2019
DOI: 10.1186/s12929-019-0576-z
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of propofol associated with the inhibition of hypoxia inducible factor and inflammasome in complex regional pain syndrome

Abstract: Background Complex regional pain syndrome (CRPS) is related to microcirculation impairment caused by tissue hypoxia and peripheral cytokine overproduction in the affected human limb and chronic post-ischemic pain (CPIP) is considered as an animal model for this intractable disease. Previous studies suggest that the pathogenesis of CPIP involves the hypoxia inducible factor-1α (HIF-1α) and an exaggerated regional inflammatory and free radical response. The inhibition of HIF-1α is known to reliev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Preclinical data suggest that propofol-based TIVA could have an analgesic effect. Possible antinociceptive mechanisms include; suppression of proinflammatory cytokines, inhibition of free radicals and hypoxia inducible factor, inhibition of Nmethyl-D-aspartic acid (NMDA) receptors, inhibition of the dorsal horn neurons of the spinal cord, and inhibition of the cannabinoid receptors CB1 and CB2 [20][21][22][23][24]. Since experimental data have shown that propofol effects pain modulation and processing, a group of investigators exposed healthy volunteers to continue propofol infusion and assessed their pain score.…”
Section: Postoperative Painmentioning
confidence: 99%
“…Preclinical data suggest that propofol-based TIVA could have an analgesic effect. Possible antinociceptive mechanisms include; suppression of proinflammatory cytokines, inhibition of free radicals and hypoxia inducible factor, inhibition of Nmethyl-D-aspartic acid (NMDA) receptors, inhibition of the dorsal horn neurons of the spinal cord, and inhibition of the cannabinoid receptors CB1 and CB2 [20][21][22][23][24]. Since experimental data have shown that propofol effects pain modulation and processing, a group of investigators exposed healthy volunteers to continue propofol infusion and assessed their pain score.…”
Section: Postoperative Painmentioning
confidence: 99%
“…Propofol, an ultra-fast-acting intravenous anesthetic with anti-inflammatory and antioxidant properties [59, 60] and few adverse effects [75], has been widely used in clinical applications. Among the widely used anesthetics, accumulated data suggest that it has a protective effect against renal ischemia/reperfusion injury (IRI) [76].…”
Section: Protective Effects and The Latest Research Of Anesthetic On ...mentioning
confidence: 99%
“…In another clinical study, Yoo et al demonstrated a significant reduction in the incidence and severity of AKI in CPB patients undergoing valvular heart surgery using propofol anesthesia compared to sevoflurane. It was also reported that postoperative cystatin C, serum IL-6, C-reactive protein, and fractional neutrophil count were significantly decreased [10], which may be related to the anti-inflammatory property of propofol [60]. However, due to the limitations of the experiment such as the small sample size, the effect of propofol on AKI has always been controversial.…”
Section: Protective Effects and The Latest Research Of Anesthetic On ...mentioning
confidence: 99%
“…[11][12][13] More recently, propofol administered after CPIP induction was shown to attenuate pain by inhibiting free radical, hypoxia inducible factor and inflammasome. 14 However, the pain signalling mechanism was mediated via peripheral tissues and not at the spinal cord level. Propofol may be a potential therapeutic option for reducing CRPS-induced pain, but centrally mediated pain mechanisms have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%